Better outcomes from exercise-related out-of-hospital cardiac arrest in males and in the young: findings from the Swedish Registry of Cardiopulmonary Resuscitation. Issue 18 (19th February 2022) - Frisk Torell, Matilda; Strömsöe, Anneli; Herlitz, Johan; Claesson, Andreas; Rawshani, Araz; Borjesson, Mats
Abstract : Background: Survival from out-of-hospital cardiac arrest (OHCA) is higher if the arrest is witnessed and occurs during exercise, however, there is contradicting data on prognosis with regards to sex and age. The purpose of this study was to compare the outcomes and circumstances of exercise-related OHCA in different age groups and between sexes in a large unselected population. Methods: Data from exercise-related OHCAs reported to the Swedish Registry of Cardiopulmonary Resuscitation from 2011 to 2014 and from 2016 to 2018 were analysed. All cases of exercise-related OHCA in which emergency medical services attempted resuscitation were included. The primary outcome was survival to 30 days. Results: In total, 635 cases of exercise-related OHCA outside of the home were identified. The overall 30-day survival rate was 44.5% with highest survival rate in the age group 0–35 years, compared with 36–65 years and >65 years (59.6% vs 46.0% and 40.4%, p=0.01). A subgroup analysis of 0–25 years showed a survival rate of 68.8%. Exercise-related OHCA in females (9.1% of total) were witnessed to a lower extent (66.7% vs 79.6%, p=0.03) and median time to cardiopulmonary resuscitation (CPR) was longer (2.0 vs 1.0 min, p=0.001) than in males. Females also had lower rates of ventricular fibrillation (43.4% vs 64.7%, p=0.003) and a lower 30-day survival rate (29.3% vs 46.0%, p=0.02). Conclusion: In exercise-related OHCA, younger victims have a higher survival rate. Exercise-related OHCA in females was rare, however, survival rates were lower compared with males and partly explained by a lower proportion of witnessed events, longer time to CPR and lower frequency of a shockable rhythm.